Effect of Long-Term Periodontal Care on Hemoglobin A1c in Type 2 Diabetes. (April 2016) - Merchant, A.T.; Georgantopoulos, P.; Howe, C.J.; Virani, S.S.; Morales, D.A.; Haddock, K.S.
This was a prospective cohort study evaluating 126, 805 individuals with diabetes and periodontal disease receiving care at all Veterans Administration medical centers and clinics in the United States from 2005 through 2012. The exposures were periodontal treatment at baseline (PT0 ) and at follow-up (PT2 ). The outcomes were change in HbA1c following initial treatment (ΔHbA1c1 ) and follow-up treatment (ΔHbA1c2 ), and diabetes control was defined as HbA1c at <7% and <9% following initial and follow-up treatment, respectively. Marginal structural models were used to account for potential confounding and selection bias. The objective was to evaluate the impact of long-term treatment of periodontal disease on glycemic control among individuals with type 2 diabetes. Participants were 64 y old on average, 97% were men, and 71% were white. At baseline, the average diabetes duration was 4 y, 12% of participants were receiving insulin, and 60% had HbA1c <7%. After an average 1.7 y of follow-up, the mean HbA1c increased from 7.03% to 7.21%. About 29.4% of participants attended their periodontal maintenance visit following baseline. Periodontal treatment at baseline and follow-up reduced HbA1c by −0.02% and −0.074%, respectively. Treatment at follow-up increased the likelihood of individuals achieving diabetes control by 5% and 3% at the HbA1c <7% and HbA1c <9% thresholds, respectively, and was observed even among never smokers. HbA1c reduction after periodontal treatment at follow-up was greater (ΔHbA1c2 = −0.25%) among individuals with higher baseline HbA1c. Long-term periodontal care provided in a clinical setting improved long-term glycemic control among individuals with type 2 diabetes and periodontal disease.